Optimizing FEC Transmission Strategy for Minimizing Delay in Lossless Sequential Streaming - Mehrotra, Sanjeev; Li, Jin; Huang, Ying-zong (IEEE Transactions on Multimedia, 2011)
As Cloud Computing is taking off, the presence of high performance interactive Internet applications is exploding. By nature, these applications require responsive client-server data exchange and lossless, in-order delivery. Previous work has shown that by using forward error correction (FEC), it is possible to reduce the data streaming latency caused by retransmissions of lost packets. However, the prior schemes only send FEC packets when there are no original packets pending transmission. In this paper, we further expand the hybrid FEC-ARQ protocol and show that sometimes, the transmission latency can be further reduced by preempting original data packets with FEC packets. We have formulated the decision of whether to send new original data packets, FEC packets, or resend original data packets as a transmission policy. An optimal transmission policy is selected to minimize the delay experienced by the application subject to a constraint on the amount of overhead. By using this optimal policy, we significantly improve the delay performance over straightforward FEC schemes while controlling the amount of overhead due to FEC.